Ethylene polymer, stretched molded article and microporous film

By controlling the specific weight average molecular weight and motility component ratio in ethylene polymer, the problems of low heat shrinkability and porosity maintenance of microporous membranes in high-speed production are solved, and excellent appearance and productivity improvement are achieved.

CN108290976BActive Publication Date: 2024-12-17ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201780003765.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-11-08
Filing Date
2017-10-25
Publication Date
2024-12-17
Estimated Expiration
2037-10-25

AI Technical Summary

Technical Problem

In the manufacturing process of microporous membranes for secondary batteries, it is difficult to maintain a balance between low heat shrinkability and porosity during high-speed production, while avoiding the problems of poor appearance such as unevenness, stripes and white spots.

Method used

Using ethylene polymers with specific weight average molecular weight and motility component ratios, the motility component ratio of the ethylene polymer is controlled by pulsed NMR measurement and polymerization conditions to achieve low heat shrinkage and porosity maintenance while suppressing mold accumulation. The emergence of

Benefits of technology

Under high-speed production conditions, the ethylene polymer microporous membrane has excellent appearance, balanced porosity and heat shrinkability, which improves productivity and membrane quality, and extends the operating life of the processing machine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0001643481350000251
    Figure GDA0001643481350000251
Patent Text Reader

Abstract

The present invention provides an ethylene polymer, wherein the weight average molecular weight (Mw) of the ethylene polymer is 200,000 to 3,000,000 inclusive, and when a three-component approximation is performed on free induction decay at 130° C. measured by a solid echo method of pulsed NMR, the proportion of a component with the lowest mobility (α130) is 40% to 60% inclusive, and the ratio β / γ of a component with intermediate mobility (β) to a component with the highest mobility (γ) is 1.0 to 4.0 inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ethylene polymer, and a stretched molded article and a microporous film comprising the ethylene polymer. Background Art

[0002] Ethylene polymers are used for various purposes such as films, sheets, microporous membranes, fibers, and molded bodies. In particular, high molecular weight ethylene polymers are used as raw materials for microporous membranes for secondary batteries represented by lead-acid batteries and lithium-ion batteries. The properties required for microporous membranes for lithium-ion batteries include insulation, ion permeability, pore sealing, etc. In addition, in order to prevent short circuits caused by shrinkage of the membrane during battery assembly and thermal shrinkage of the membrane at high temperatures, the microporous membrane for lithium-ion batteries is required to have low thermal shrinkage. Therefore, as a method for suppressing thermal shrinkage, the methods described in Patent Documents 1 to 3 are proposed.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 4098401

[0006] Patent Document 2: Japanese Patent Application Publication No. 2013-199597

[0007] Patent Document 3: Japanese Patent No. 5586152 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, in recent years, in the field of microporous membranes for secondary batteries, while high demand is growing, there is a strong demand for low-cost components, and it is expected to improve not only membrane performance but also productivity. In general, in the manufacturing process of microporous membranes, annealing is performed in order to suppress shrinkage in the use environment and thermal shrinkage in a high temperature environment by relaxing tensile stress. The relaxation of tensile stress is easier to perform at higher temperatures. Therefore, in order to improve productivity, it is thought that stress relaxation is performed in a short time by increasing the annealing temperature, but in the case of annealing at high temperatures, there is a problem of pore closure and reduced porosity. The technology disclosed in citations 1 to 3 does not mention the effects related to high productivity, and it is expected to take into account the maintenance of low thermal shrinkage and porosity. In addition, for products such as microporous membranes, it is required that there is no unevenness, streaks, white spots caused by unmelted materials, and other poor appearance.

[0010] The problem to be solved by the present invention is to provide an ethylene polymer which can produce a microporous membrane or the like having excellent appearance and an excellent balance between maintaining porosity and maintaining low thermal shrinkage even in high-speed production, and a stretched molded body comprising the ethylene polymer.

[0011] Means used to solve problems

[0012] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that an ethylene polymer having a specified weight-average molecular weight, a specified composition fraction of a component with the lowest mobility (α130) obtained by performing a three-component approximation on free induction decay at 130°C measured by a solid echo method using pulsed NMR, and a specified value for the composition ratio β / γ of a component with intermediate mobility (β) to a component with the highest mobility (γ) can solve the above-mentioned problems, thereby completing the present invention.

[0013] That is, the present invention is as follows. [1]

[0015] An ethylene polymer, wherein

[0016] The weight average molecular weight (Mw) of the ethylene polymer is 200,000 or more and 3,000,000 or less,

[0017] In the case of a three-component approximation of the free induction decay at 130°C measured by a solid echo method of pulsed NMR, the proportion of the component with the lowest motility (α130) is greater than 40% and less than 60%, and the ratio of the proportion of the component with intermediate motility (β) to the proportion of the component with the highest motility (γ) (β / γ) is greater than 1.0 and less than 4.0. [2]

[0019] The ethylene polymer as described in [1], wherein

[0020] The ratio (α130 / α30) of the ratio of the component with the lowest motility (α130) measured at 130° C. to the ratio of the component with the lowest motility (α30) measured at 30° C. by the solid echo method of the pulsed NMR is 0.1 or more and 0.65 or less. [3]

[0022] The ethylene polymer according to [1] or [2], wherein

[0023] The weight average molecular weight (Mw) of the ethylene polymer is 250,000 or more and 800,000 or less. [4]

[0025] The ethylene polymer according to any one of [1] to [3], wherein

[0026] The molecular weight distribution (Mw / Mn) of the ethylene polymer is 5 or more and 15 or less. [5]

[0028] The ethylene polymer according to any one of [1] to [4], wherein

[0029] The content of one or more elements selected from the group consisting of Ti, Mg, and Al is 50 ppm or less. [6]

[0031] The ethylene polymer according to any one of [1] to [5], which is in the form of powder. [7]

[0033] The ethylene polymer according to any one of [1] to [6], wherein

[0034] The ratio D90 / D10 of the particle size of the ethylene polymer measured by a laser particle size analyzer is 1.30 to 1.80. [8]

[0036] A stretched molded article comprising the ethylene polymer described in any one of [1] to [7]. [9]

[0038] A microporous film comprising the ethylene polymer described in any one of [1] to [7].

[0039] Effects of the Invention

[0040] According to the present invention, an ethylene polymer having excellent appearance even in high-speed production and excellent balance between porosity and low thermal shrinkage, and a stretched molded product comprising the ethylene polymer can be provided. In addition, surprisingly, by using the ethylene polymer of the present invention, the generation of deposits on the mold of the processing machine is suppressed, and the long-term operation of the manufacturing machine of the stretched molded product and the improvement of the film quality are achieved. DETAILED DESCRIPTION

[0041] Hereinafter, a mode for implementing the present invention (hereinafter also referred to as "this embodiment") will be described in detail. It should be noted that the present invention is not limited to this embodiment, and can be implemented in various modifications within the scope of the gist thereof.

[0042] [Ethylene polymer]

[0043] The weight average molecular weight (Mw) of the ethylene polymer of the present embodiment is greater than or equal to 200,000 and less than or equal to 3,000,000, and when a three-component approximation is performed on the free induction decay at 130°C measured by a solid echo method using pulsed NMR, the proportion of the component with the lowest mobility (α130) is greater than or equal to 40% and less than or equal to 60%, and the ratio β / γ of the proportion of the component with intermediate mobility (β) to the proportion of the component with the highest mobility (γ) is greater than or equal to 1.0 and less than or equal to 4.0.

[0044] The above requirements are described below.

[0045] (Weight average molecular weight (Mw))

[0046] The weight average molecular weight (Mw) of the ethylene polymer of the present embodiment is more than 200000 and less than 3000000, preferably more than 220000 and less than 1500000, more preferably more than 250000 and less than 800000, further preferably more than 250000 and less than 750000. The Mw of ethylene polymer can be regulated by using the catalyst described later, appropriately adjusting the polymerization conditions, etc. Specifically, the weight average molecular weight (Mw) can be regulated by having hydrogen in the polymerization system, changing the polymerization temperature, etc.

[0047] When the weight average molecular weight (Mw) is 200,000 or more, the proportion of the component (α130) with the lowest mobility measured by pulse NMR at 130°C can be adjusted to be large, thereby achieving the desired low heat shrinkage. On the other hand, when the Mw is 3,000,000 or less, dissolution and stretching in a solvent become easy, and the appearance of the film is improved.

[0048] The weight average molecular weight (Mw) of the ethylene polymer of the present embodiment can be obtained by measuring an o-dichlorobenzene solution in which the ethylene polymer is dissolved using gel permeation chromatography (hereinafter also referred to as "GPC"), and obtaining the weight average molecular weight (Mw) of the ethylene polymer based on a calibration curve prepared using commercially available monodisperse polystyrene. More specifically, the measurement can be performed using the method described in the Examples.

[0049] (Three-component approximation of free induction decay obtained by pulsed NMR)

[0050] The ethylene polymer of the present embodiment is approximated into three components, namely, a component with the lowest mobility (α), a component with intermediate mobility (β), and a component with the highest mobility (γ), by fitting the free induction decay (M(t)) of the ethylene polymer obtained by the solid echo method in pulse NMR measured at a specific temperature using Formula 1 and the least squares method.

[0051] M(t)=αexp(-(1 / 2)(t / T α ) 2 )sinbt / bt+βexp(-(1 / Wa)(t / T β ) Wa )+γexp(-t / T γ ) Formula 1

[0052] α: Fraction of α component (%)

[0053] T α : Relaxation time of the α component (milliseconds)

[0054] β: Fraction of β component (%)

[0055] T β : Relaxation time of the β component (milliseconds)

[0056] γ: The composition fraction of γ component (%)

[0057] T γ : Relaxation time of the γ component (milliseconds)

[0058] t: observation time (milliseconds)

[0059] Wa: Shape coefficient (1<Wa<2)

[0060] b: shape coefficient (0.1<b<0.2)

[0061] More specifically, pulse NMR can be measured by the method described in Examples.

[0062] (The component with the lowest mobility in 130°C pulse NMR (α130))

[0063] The proportion of the component with the lowest mobility (α130) (hereinafter also referred to as component (α130), component with the lowest mobility (α130)) in the case of a three-component approximation of the free induction decay obtained by a solid echo method in pulse NMR measured at 130°C is greater than 40% and less than 60%, preferably greater than 40% and less than 55%.

[0064] There is no particular limitation on the method for controlling the proportion of (α130) with the lowest motility, and examples thereof include: adjusting the weight average molecular weight to be greater than 200,000 and less than 3,000,000; maintaining the temperature of the ethylene polymer slurry at greater than 65°C until the ethylene polymer is separated from the solvent by a centrifuge during the production of the ethylene polymer; adding humidified nitrogen to the ethylene polymer after centrifugal separation; etc.

[0065] When the ratio of component (α130) is 40% or more, molecular motion at high temperature can be suppressed to achieve low heat shrinkage. On the other hand, when the ratio of component (α130) is 60% or less, a microporous film having excellent heat shrinkage and film appearance can be obtained.

[0066] (Ratio of the medium-mobility component (β) to the high-mobility component (γ) in 130°C pulsed NMR (β / γ))

[0067] In the case of three-component approximation of the free induction decay obtained by the solid echo method in pulse NMR measured at 130° C., the ratio β / γ of the component with medium mobility (β) to the component with the highest mobility (γ) is greater than 1.0 and less than 4.0, preferably greater than 1.0 and less than 3.0, and more preferably greater than 1.0 and less than 2.5.

[0068] Methods for controlling the ratio β / γ of the component with medium mobility to the component with the highest mobility include, for example: adjusting the weight average molecular weight to be greater than 200,000 and less than 3,000,000; making the ethylene feed port and the catalyst feed port in the polymerizer as close as possible; adjusting the slurry concentration in the polymerizer to be greater than 30% and less than 50%; etc.

[0069] If β / γ is 1.0 or more, the change in porosity during annealing can be suppressed within a desired range, and deposits on the mold can be suppressed. On the other hand, if β / γ is 4.0 or less, a microporous membrane having an excellent appearance can be obtained.

[0070] (The ratio of the low mobility component (α130) in 130°C pulse NMR to the low mobility component (α30) in 30°C pulse NMR α130 / α30)

[0071] The ratio of the ratio of the lowest mobility component (α130) when three-component approximation is performed on the free induction decay obtained by the solid echo method in the pulse NMR measured at 130°C to the ratio of the lowest mobility component (α30) when three-component approximation is performed on the free induction decay obtained by the solid echo method in the pulse NMR measured at 30°C (α130 / α30) is preferably greater than 0.1 and less than 0.65, more preferably greater than 0.4 and less than 0.65, and further preferably greater than 0.55 and less than 0.60.

[0072] Examples of a method for controlling the ratio (α130 / α30) include a method of allowing the slurry after polymerization to remain for 2 hours or longer and then subjecting it to centrifugal separation.

[0073] When the ratio (α130 / α30) is 0.1 or more, the porosity at the time of annealing at 125° C. tends to be maintained. On the other hand, when the ratio (α130 / α30) is 0.65 or less, a film with less porosity variation can be obtained.

[0074] The above ratio (α130 / α30) can be obtained by fitting the free induction decay (M(t)) of the ethylene polymer obtained by the solid echo method in the pulse NMR measured at 30°C and 130°C using the above formula 1 and the least squares method, thereby obtaining the above ratio (α130 / α30). Specifically, it can be obtained by the method described in the examples.

[0075] As the ethylene polymer of the present embodiment, there is no particular limitation, and examples include: ethylene homopolymers, and / or copolymers of ethylene and other comonomers. As other comonomers, there is no particular limitation, and examples include: α-olefins, vinyl compounds. As the above-mentioned α-olefins, there is no particular limitation, and examples include: α-olefins with 3 to 20 carbon atoms, specifically, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, etc. In addition, as the above-mentioned vinyl compounds, there is no particular limitation, and examples include: vinyl cyclohexane, styrene and its derivatives. In addition, as other comonomers, non-conjugated polyenes such as 1,5-hexadiene and 1,7-octadiene can also be used as needed. The above-mentioned copolymer can be a ternary random polymer. Other comonomers can be used alone or in combination of two or more.

[0076] When the ethylene polymer of the present embodiment contains units derived from comonomers (hereinafter, also referred to as comonomer units), the content of the comonomer units in the ethylene polymer is preferably 0.01 mol% to 5 mol%, more preferably 0.01 mol% to 2 mol%, and further preferably 0.01 mol% to 1 mol%.

[0077] The molecular weight distribution (Mw / Mn) of the ethylene polymer of the present embodiment is preferably 5.0 or more and 15.0 or less, more preferably 5.5 or more and 14.0 or less, and even more preferably 6.0 or more and 12.0 or less.

[0078] The molecular weight distribution of the ethylene polymer can be adjusted to be small by using a catalyst described later or by keeping the conditions in the polymerization system (hydrogen concentration, temperature, ethylene pressure, etc.) constant. On the other hand, as a method for adjusting the molecular weight distribution of the ethylene polymer to be large, there can be cited methods such as changing the conditions in the polymerization in batch polymerization (for example, changing the concentration of hydrogen as a chain transfer agent, changing the temperature, etc. in the polymerization), using a plurality of reactors in continuous polymerization and changing the conditions in the polymerization system.

[0079] If the molecular weight distribution is more than 5.0, the ethylene polymer of the present embodiment has better molding processability, and as a result, the appearance of the film is excellent. On the other hand, if the molecular weight distribution is below 15.0, the composition of the molecular weight is uniform, and as a result, the appearance of the film is excellent.

[0080] The molecular weight distribution (Mw / Mn) of the ethylene polymer of the present embodiment can be obtained by measuring an o-dichlorobenzene solution in which the ethylene polymer is dissolved using gel permeation chromatography (hereinafter also referred to as "GPC"), and obtaining the molecular weight distribution (Mw / Mn) of the ethylene polymer based on a calibration curve prepared using commercially available monodisperse polystyrene. More specifically, the measurement can be performed using the method described in the Examples.

[0081] The content of one or more elements selected from the group consisting of Ti, Mg, and Al of the ethylene polymer of the present embodiment (hereinafter, also referred to as residual catalyst ash) is preferably below 50ppm, more preferably below 40ppm, and further preferably below 30ppm. In addition, the less residual catalyst ash in the ethylene polymer, the better. By having the residual catalyst ash within the above range, there is a tendency that low thermal shrinkage is more excellent. It should be noted that the content of Ti, Mg, and Al can be measured by the method described in the embodiment. In order to control the residual catalyst ash less, it can be listed as follows: regulating the pressure, utilizing centrifugal separation to separate the ethylene polymer from the solvent, etc.

[0082] The content of one or more elements selected from the group consisting of Ti, Mg, and Al is preferably the total content of Ti, Mg, and Al.

[0083] The shape of the ethylene polymer of the present embodiment is preferably spherical powder.

[0084] The particle size distribution (D90 / D10) of the ethylene polymer of the present embodiment is preferably 1.30 or more and 1.80 or less, and more preferably 1.40 to 1.70. When the particle size distribution is within the above range, the appearance of the film tends to be more excellent.

[0085] In addition, the particle size distribution is a value obtained using a laser particle size distribution measuring instrument, and can be measured using, for example, SALD-2100 manufactured by Shimadzu Corporation.

[0086] The above-mentioned particle size distribution (D90 / D10) refers to: in a particle size distribution table in which the diameter of the particles is recorded on the horizontal axis and the percentage of the amount (number) is recorded on the vertical axis, the ratio of the particle size value (D90) when the cumulative value is 90% to the particle size value (D10) when the cumulative value is 10%.

[0087] Specifically, the particle size distribution (D90 / D10) can be adjusted to a range of 1.30 or more and 1.80 or less by using a catalyst described later or by using a method such as batch polymerization.

[0088] [Catalyst ingredients]

[0089] The catalyst component used for producing the ethylene polymer of the present embodiment is not particularly limited, and the ethylene polymer can be produced using, for example, Ziegler-Natta catalysts and metallocene catalysts disclosed in Japanese Patent Nos. 5782558, 5829257, 4868853, and JP-A-10-218933.

[0090] [Method for producing ethylene polymer]

[0091] Examples of the polymerization method in the method for producing the ethylene polymer of the present embodiment include a method of (co)polymerizing ethylene or a monomer containing ethylene by a suspension polymerization method or a gas phase polymerization method.

[0092] Among them, the suspension polymerization method is preferred because it can effectively remove the heat of polymerization. In the suspension polymerization method, an inert hydrocarbon medium can be used as a medium, and the olefin itself can also be used as a solvent.

[0093] The above-mentioned inert hydrocarbon medium is not particularly limited, and specifically includes: aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, kerosene, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, dichloromethane, etc. and mixtures thereof, etc.

[0094] The polymerization temperature in the method for producing the ethylene polymer of the present embodiment is usually preferably 30° C. or higher and 100° C. or lower, more preferably 35° C. or higher and 90° C. or lower, and further preferably 40° C. or higher and 80° C. or lower. If the polymerization temperature is 30° C. or higher, efficient production can be performed industrially. On the other hand, if the polymerization temperature is 100° C. or lower, continuous stable operation can be achieved.

[0095] The polymerization pressure in the manufacture method of the ethylene polymer of the present embodiment is usually preferably more than normal pressure and below 2MPa, more preferably more than 0.1MPa and below 1.5MPa, further preferably more than 0.1MPa and below 1.0MPa.Being more than normal pressure by the polymerization pressure, there is a tendency to obtain ethylene polymers with low residual catalyst ash content, and being below 2MPa by the polymerization pressure, there is a tendency to stably produce ethylene polymers when not producing blocky dirt.In addition, from the viewpoint of controlling β / γ, the ethylene feed port is preferably as close to the catalyst feed port as possible.

[0096] As described above, the ratio of α130 of the ethylene polymer of the present embodiment is 40% or more and 60% or less, and β / γ is 1.0 or more and 4.0 or less. That is, when the ethylene polymer is divided into three components with different molecular mobility, it is necessary to appropriately control the amount of each component. For this reason, it is important not to hinder crystallization and to allow molecular entanglement to occur.

[0097] From the viewpoint of not hindering crystallization, it is preferred to keep the temperature of the ethylene polymer slurry at 65° C. or higher until the slurry after polymerization is separated into the ethylene polymer and the solvent by a centrifugal separator. By keeping the temperature of the ethylene polymer slurry at 65° C. or higher, impurities can be effectively removed during centrifugal separation, and the orderliness of the polymer in the solid phase can be improved.

[0098] In addition, from the viewpoint of the entanglement of molecules, it is preferred that the slurry concentration in the polymerization system is adjusted to more than 30 mass % and less than 50 mass %, more preferably adjusted to more than 40 mass % and less than 50 mass %. By adjusting the slurry concentration to more than 30 mass %, the temperature near the reaction site on the catalyst during polymerization can be appropriately kept higher, with a tendency to improve the constraint between molecules by promoting the entanglement of molecules. On the other hand, by adjusting the slurry concentration to less than 50 mass %, there is a tendency to stably produce ethylene polymers without producing blocky scale.

[0099] In addition, the α130 / α30 of the ethylene polymer of the present embodiment is preferably 0.1 or more and 0.65 or less. In order to obtain such an ethylene polymer, for example, it is preferred that the slurry of the ethylene polymer is retained in a buffer tank or the like for 2 hours or more until the slurry of the ethylene polymer is separated into the ethylene polymer and the solvent by a centrifugal separator. By retaining the polymer slurry for 2 hours or more, the composition fraction of the lowest mobility component (α30) of the ethylene polymer at 30° C. increases, and the ratio of α130 / α30 can be adjusted to 0.1 or more and 0.65 or less.

[0100] For the solvent separation method in the manufacture method of the ethylene polymer of the present embodiment, decantation, centrifugal separation, filter filtration method etc. can be utilized to carry out, and from the viewpoint of the separation efficiency of ethylene polymer and solvent, centrifugal separation is preferred. The amount of the solvent contained in the ethylene polymer after solvent separation is not particularly limited, and relative to the weight of the ethylene polymer, is preferably below 70 mass %, more preferably below 60 mass %, and further preferably below 50 mass %. By drying and removing the solvent under a small amount of state with the solvent contained in the ethylene polymer, there is a tendency that the metal component, low molecular weight component etc. contained in the solvent are not easy to remain in the ethylene polymer.

[0101] The deactivation of the catalyst used for synthesizing the ethylene polymer of the present embodiment is not particularly limited, but is preferably carried out after the ethylene polymer is separated from the solvent from the viewpoint of controlling the composition fraction of α130. By introducing a reagent for deactivating the catalyst after separation from the solvent, the precipitation of low molecular weight components, catalyst components, etc. contained in the solvent can be reduced.

[0102] Examples of the agent for deactivating the catalyst system include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, and alkynes.

[0103] The drying temperature in the method for producing the ethylene polymer of the present embodiment is usually preferably 50°C or more and 150°C or less, more preferably 50°C or more and 130°C or less, and further preferably 50°C or more and 100°C or less. If the drying temperature is 50°C or more, effective drying can be performed. On the other hand, if the drying temperature is 150°C or less, drying can be performed under the state of suppressing the decomposition and crosslinking of the ethylene polymer. In the present embodiment, in addition to the above-mentioned components, other known components useful for the manufacture of the ethylene polymer may also be included.

[0104] In the method for producing an ethylene polymer of the present embodiment, in order to control the polymerization average molecular weight, molecular weight distribution (Mw / Mn), and adjust the ratio of the component with the lowest mobility (α30, α130), the component with intermediate mobility (β), and the component with the highest mobility (γ), it is preferred that hydrogen exists in the polymerization system.

[0105] Hydrogen can be continuously supplied to the polymerization reactor by a pump. The hydrogen concentration is preferably 10 to 20 mol %, more preferably 12 to 18 mol %, based on ethylene in the gas phase.

[0106] [additive]

[0107] Furthermore, the ethylene polymer of the present embodiment may contain additives such as a neutralizer, an antioxidant, and a light stabilizer.

[0108] The neutralizing agent is used as a chlorine trapping agent or a molding processing aid contained in the ethylene polymer. The neutralizing agent is not particularly limited, and specifically, stearates of alkaline earth metals such as calcium, magnesium, and barium can be cited. The content of the neutralizing agent is not particularly limited, but is preferably 5000 ppm or less, more preferably 4000 ppm or less, and further preferably 3000 ppm or less.

[0109] The antioxidant is not particularly limited, and specifically includes phenolic antioxidants such as butylated hydroxytoluene, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. The content of the antioxidant is not particularly limited, but is preferably 5000 ppm or less, more preferably 4000 ppm or less, and further preferably 3000 ppm or less.

[0110] The light stabilizer is not particularly limited, and specific examples thereof include benzotriazole-based light stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole, and hindered amine-based light stabilizers such as bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}]. The content of the light stabilizer is not particularly limited, but is preferably 5000 ppm or less, more preferably 4000 ppm or less, and even more preferably 3000 ppm or less.

[0111] In the ethylene polymer of present embodiment, can blend different ethylene polymers such as viscosity-average molecular weight, molecular weight distribution, also can blend other resins such as low-density ethylene polymer, linear low-density ethylene polymer, polypropylene, polystyrene.In addition, even if the ethylene polymer of present embodiment is powdery or granular, also can use compatibly.

[0112] [use]

[0113] The molded body comprising the ethylene polymer of the present embodiment can be suitably used as a stretched molded body, a microporous membrane, or a battery separator. As such a molded body, for example, a secondary battery separator, particularly a lithium ion secondary battery separator, a high-strength fiber, a microporous membrane, and gel spinning can be cited.

[0114] Example

[0115] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples at all.

[0116] [Reference Example] Catalyst Synthesis Example

[0117] (Preparation of solid catalyst component [A])

[0118] 1600 mL of hexane was added to an 8 L stainless steel autoclave that had been fully purged with nitrogen. While stirring at 5°C, 800 mL of a 1 mol / L titanium tetrachloride hexane solution and 800 mL of a 1 mol / L AlMg5(C4H9) solution were added simultaneously over 4 hours. 11 After the addition, the temperature was slowly raised and the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1600 mL of the supernatant was removed and washed five times with 1600 mL of hexane to prepare a solid catalyst component [A].

[0119] (Preparation of solid catalyst component [B])

[0120] (1) (B-1) Synthesis of carrier

[0121] 1000 mL of a 2 mol / L hexane solution of hydroxytrichlorosilane was placed in an 8 L stainless steel autoclave that had been fully purged with nitrogen, and 2550 mL of a solution of AlMg5(C4H9) was added dropwise over 4 hours while stirring at 65°C. 11 A hexane solution of an organomagnesium compound represented by (OC4H9)2 (corresponding to 2.68 mol of magnesium) was added, and the reaction was continued while stirring at 65°C for 1 hour. After the reaction was completed, the supernatant was removed and washed four times with 1800 mL of hexane to obtain a carrier (B-1).

[0122] (2) Preparation of solid catalyst component [B]

[0123] In 1970 mL of hexane slurry containing 110 g of the above-mentioned (B-1) carrier, 110 mL of a 1 mol / L titanium tetrachloride hexane solution and 110 mL of a 1 mol / L diethylaluminum chloride hexane solution were added simultaneously over 1 hour while stirring at 50° C. After the addition, the reaction was continued at 50° C. for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed and washed twice with 1100 mL of hexane to prepare a solid catalyst component [B].

[0124] (Preparation of solid catalyst component [C])

[0125] In 1970 mL of hexane slurry containing 110 g of the above-mentioned (B-1) carrier, 110 mL of a 1 mol / L titanium tetrachloride hexane solution and 110 mL of a 1 mol / L AlMg5(C4H9) solution having the composition formula were added simultaneously over 1 hour while stirring at 10°C. 11A hexane solution of an organomagnesium compound represented by (OSi(C2H5)H)2 was added. After the addition, the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1100 mL of the supernatant was removed and washed twice with 1100 mL of hexane to prepare a solid catalyst component [C].

[0126] (Preparation of solid catalyst component [D])

[0127] (1) (D-1) Synthesis of carrier

[0128] As a precursor of the carrier (D-1), a catalyst having an average particle size of 7 μm and a specific surface area of ​​660 m 2 / g, pore volume 1.4mL / g, and compressive strength 7MPa of silica.

[0129] The heat-treated silica (130 g) was dispersed in 2500 mL of hexane in an 8 L autoclave purged with nitrogen to obtain a slurry. 195 mL of a hexane solution (concentration 1 M) of triethylaluminum as a Lewis acidic compound was added to the obtained slurry under stirring at 20° C. Then, the mixture was stirred for 2 hours to react the triethylaluminum with the surface hydroxyl groups of the silica to prepare 2695 mL of a hexane slurry of the (D-1) carrier adsorbed with triethylaluminum.

[0130] (Preparation of transition metal compound component [E])

[0131] [(N-tert-butylamino)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter referred to as "complex 1") was used as the transition metal compound (E-1). In addition, a compound having the composition formula Mg(C2H5)(C4H9) (hereinafter referred to as "Mg1") was used as the organic magnesium compound (E-2).

[0132] 200 mmol of complex 1 was dissolved in 1000 mL of isoparaffin (ISOPAR E manufactured by ExxonMobil Corporation), 40 mL of a hexane solution of Mg1 (concentration 1 M) was added thereto, and hexane was further added to adjust the concentration of complex 1 to 0.1 M, thereby obtaining a transition metal compound component [E].

[0133] (Preparation of Activating Agent [F])

[0134] 17.8 g of bis(hydrogenated tallow alkyl)methylammonium-tetrakis(pentafluorophenyl)borate (hereinafter referred to as "borate") as a borate compound (F-1) was added to 156 mL of toluene and dissolved to obtain a 100 mmol / L toluene solution of the borate. 15.6 mL of a 1 mol / L hexane solution of ethoxydiethylaluminum (F-2) was added to the toluene solution of the borate at room temperature, and toluene was further added to adjust the borate concentration in the solution to 70 mmol / L. Then, the mixture was stirred at room temperature for 1 hour to prepare an activator [F] containing a borate.

[0135] (Preparation of solid catalyst [D])

[0136] In 2695 mL of a slurry of the carrier (D-1) obtained by the above operation, while stirring at 400 rpm at 25°C, 219 mL of an activator [F] obtained by the above operation and 175 mL of a transition metal compound component [E] were added simultaneously from another pipeline using a metering pump over 30 minutes, and the reaction was continued for 3 hours to prepare a solid catalyst [D].

[0137] (Preparation of liquid component [G])

[0138] Using the composition formula AlMg6(C2H5)3(C4H9) 12 (hereinafter, abbreviated as "Mg2") as the organic magnesium compound (G-1).

[0139] In a 200 mL flask, 40 mL of hexane and 38.0 mmol of Mg2 based on the total amount of Mg and Al were added while stirring, and 40 mL of hexane containing 2.27 g (37.8 mmol) of methyl hydrogen polysiloxane (viscosity at 25°C, 20 centistokes; hereinafter referred to as "siloxane compound") was added while stirring at 20°C, and then the temperature was raised to 80°C and reacted for 3 hours while stirring, thereby preparing a liquid component [G].

[0140] [Example 1]

[0141] Hexane, ethylene, hydrogen and catalyst are continuously supplied to a container-type 300L polymerization reactor with a stirring device. The polymerization pressure is 0.5MPa. The polymerization temperature is maintained at 80°C by jacket cooling. A solid catalyst component [A] and triisobutylaluminum as a cocatalyst are used. Triisobutylaluminum is added to the polymerization reactor at a rate of 10 mmol / hour. The solid catalyst component [A] is supplied so that the production rate of ethylene polymer reaches 10kg / hour and the slurry concentration in the polymerization reactor reaches 40% by mass. Hexane is supplied so that the liquid level remains constant. Hydrogen is continuously supplied with a pump so that the hydrogen concentration of ethylene relative to the gas phase reaches 15 mol%. The catalyst activity is 75000g-PE / g-solid catalyst component [A]. The polymerization slurry is continuously extracted to a flash evaporator at a pressure of 0.05MPa and a temperature of 70°C to separate unreacted ethylene and hydrogen.

[0142] Next, the polymerization slurry was retained in a buffer tank for 2 hours while maintaining the temperature at 66° C. or higher and then continuously transferred to a centrifuge to separate the polymer from the solvent, etc. The content of the solvent, etc. relative to the polymer was 45%.

[0143] The separated ethylene polymer powder was dried at 85°C while blowing nitrogen. It should be noted that in the drying process, water vapor was sprayed on the polymerized powder to deactivate the catalyst and the co-catalyst. 1000ppm of calcium stearate (manufactured by Dainichi Chemical Co., Ltd., C60) was added to the obtained ethylene polymer powder and uniformly mixed using a Henschel mixer. For the obtained ethylene polymer powder, a sieve with a mesh size of 425μm was used to remove the powder that could not pass through the sieve to obtain an ethylene polymer powder. The properties of the obtained ethylene polymer were measured using the method shown below. The results are shown in Table 1.

[0144] (Method for producing microporous membrane)

[0145] 0.3 parts by mass of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant was added to 100 parts by mass of ethylene polymer powder, and dry blending was performed using a tumbler mixer to obtain an ethylene polymer mixture. The obtained ethylene polymer mixture was replaced with nitrogen and then fed into a twin-screw extruder via a feeder under a nitrogen atmosphere. Then 150 parts by mass of liquid paraffin (P-350 (registered trademark) manufactured by Matsumura Oil Co., Ltd.) was injected into the extruder in a side-feed manner, kneaded at 200°C, extruded from a T-die provided at the front end of the extruder, and then immediately cooled and solidified with a roller cooled to 25°C, thereby forming a gel-like sheet with a thickness of 900 μm.

[0146] The gel-like sheet was stretched to 7×7 times at 120°C using a simultaneous biaxial stretching machine, and then the stretched film was immersed in methyl ethyl ketone to extract and remove liquid paraffin, and then dried. It was then annealed at 125°C for 3 minutes to obtain a microporous membrane. The physical properties of the obtained membrane were measured using the method shown below. The results are shown in Table 1.

[0147] (Methods for measuring various characteristics and properties)

[0148] (1) Molecular weight determination

[0149] 15 mL of o-dichlorobenzene was introduced into 20 mg of ethylene polymer and stirred at 150° C. for 1 hour to prepare a sample solution, and the sample solution was subjected to gel permeation chromatography (GPC) measurement under the following conditions. From the measurement results, the number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) were determined based on a calibration curve prepared using commercially available monodisperse polystyrene.

[0150] Equipment: 150-C ALC / GPC manufactured by Waters

[0151] Detector: RI detector

[0152] Mobile phase: o-dichlorobenzene (for high performance liquid chromatography)

[0153] Flow rate: 1.0mL / min

[0154] Column: A column obtained by connecting one AT-807S manufactured by Shodex and two TSK-gelGMH-H6 manufactured by Tosoh was used.

[0155] Column temperature: 140°C

[0156] (2) Pulse NMR

[0157] The composition fractions of the three components at 30° C. and 130° C. measured by a solid echo method of pulsed NMR were measured under the following conditions.

[0158] Measuring device: JNM-Mu25 manufactured by JEOL Ltd.

[0159] Observation core: 1 H

[0160] Determination: T2

[0161] Determination method: solid echo method

[0162] Pulse width: 2.2μs~2.3μs

[0163] Pulse interval: 7.0μs~9.2μs

[0164] Cumulative times: 256 times

[0165] Measuring temperature: 30℃, 50℃, 70℃, 90℃, 110℃, 130℃ (The measuring temperature is the temperature inside the sample. After the device temperature reaches the set temperature, adjust the device temperature so that the temperature inside the sample reaches the measuring temperature 5 minutes later and start the measurement)

[0166] Repeat time: 3s

[0167] Analysis method: Formula 1 was used to fit the equation using analysis software (IGOR Pro 6.3) and the equation was approximated into three components.

[0168] M(t)=αexp(-(1 / 2)(t / T α ) 2 )sinbt / bt+βexp(-(1 / Wa)(t / T β ) Wa )+γexp(-t / T γ ) Formula 1

[0169] α: Fraction of α component (%)

[0170] T α : Relaxation time of the α component (milliseconds)

[0171] β: Fraction of β component (%)

[0172] T β : Relaxation time of the β component (milliseconds)

[0173] γ: The composition fraction of γ component (%)

[0174] T γ : Relaxation time of the γ component (milliseconds)

[0175] t: observation time (milliseconds)

[0176] Wa: Shape factor

[0177] b: shape factor

[0178] (3) Residual catalyst ash (total content of Ti, Mg, and Al)

[0179] 0.2 g of sample was weighed in a Teflon (registered trademark) decomposition container, high-purity nitric acid was added, and pressure decomposition was performed using a microwave decomposition device ETHOS-TC manufactured by Milestone-General, and then the total amount was adjusted to 50 mL using pure water purified by an ultrapure water production device manufactured by Millipore, Japan, and the resulting solution was used as a test solution. For the above-mentioned test solution, an inductively coupled plasma mass spectrometer (ICP-MS) X series 2 manufactured by Thermo Fisher Scientific was used to quantify Ti, Mg, and Al using an internal standard method.

[0180] (4) Particle size distribution (D90 / D10)

[0181] D90 and D10 were measured using a laser particle size distribution measuring instrument (SALD-2100 manufactured by Shimadzu Corporation), and D90 / D10 was defined as the particle size distribution.

[0182] (5)Film thickness

[0183] The film thickness of the microporous film was measured at room temperature of 23° C. using a micro thickness gauge (model KBM (registered trademark) manufactured by Toyo Seiki Co., Ltd.).

[0184] (6) Thermal shrinkage

[0185] The microporous membrane was cut into 100 mm lengths with a width of 10 mm in the MD direction. The cut microporous membrane was placed in a hot air oven at 130°C and heated for 1 hour. The heat shrinkage rate (%) was calculated as the ratio of the length after shrinkage to the original length (100 mm).

[0186] (7) Porosity

[0187] The porosity was obtained by cutting a 10 cm × 10 cm square sample from the microporous membrane and calculating its volume (cm 3 ) and mass (g), and use them to calculate the film density (g / cm 3 ), use the following formula to calculate.

[0188] Porosity = (volume - mass / membrane density) / volume × 100

[0189] The film density was set to 0.95 g / cm 3 .

[0190] (8) Changes in thermal shrinkage and porosity

[0191] The microporous membrane obtained by changing the annealing conditions to 133°C and 60 seconds was measured for changes in heat shrinkage and porosity relative to the conditions of 125°C and 3 minutes. It should be noted that the heat shrinkage was measured by method (6) and the porosity was measured by method (7).

[0192] Change in thermal shrinkage = thermal shrinkage 125 -Heat shrinkage 133

[0193] Thermal shrinkage 125 : Thermal shrinkage after annealing at 125℃ for 3 minutes

[0194] Thermal shrinkage 133 : Thermal shrinkage after annealing at 133℃ for 1 minute

[0195] In Table 1, a case where the change in heat shrinkage was 1% or less was marked as ⊚, a case where it was more than 1% and less than 3% was marked as ◯, and a case where it was 3% or more was marked as ×.

[0196] Change in porosity = porosity 125 -Porosity 133

[0197] Porosity 125 : Porosity after annealing at 125℃ for 3 minutes

[0198] Porosity 133 : Porosity after annealing at 133℃ for 1 minute

[0199] In Table 1, a case where the porosity change was less than 5% was marked as ⊚, a case where the porosity change was 5% or more and less than 10% was marked as ◯, and a case where the porosity change was 10% or more was marked as ×.

[0200] (9) Film appearance

[0201] The microporous membrane was visually observed for every 100 m of unevenness, streaks, white spots due to unmelted matter, and other appearance defects. In Table 1, no appearance defects were observed at all as ◎, 3 or less were observed as ○, and 4 or more were observed as ×.

[0202] (10) Porosity Unevenness

[0203] For the unevenness of porosity, 10 cm × 10 cm square samples were cut from the central part and the end part of the microporous membrane in the TD direction, and the porosity difference calculated by the same method as (7) was measured. The case where the porosity difference was less than 1% was marked as ◎, the case where it was greater than or equal to 1% and less than 2% was marked as ○, and the case where it was greater than 2% was marked as ×.

[0204] (11) Mold deposits

[0205] When the film formation was carried out for 5 hours, the deposits on the die of the extruder were observed. In Table 1, the case where there was no deposit was marked as ○, and the case where there was deposit was marked as ×.

[0206] [Example 2]

[0207] In the polymerization step, the solid catalyst component [B] was used instead of the solid catalyst component [A] and the hydrogen concentration was set to 14 mol %, and the ethylene polymer powder of Example 2 was obtained by the same operation as in Example 1. The microporous membrane of Example 2 was obtained by the same operation as in Example 1.

[0208] [Example 3]

[0209] The ethylene polymer powder of Example 3 was obtained by the same operation as in Example 1 except that the hydrogen concentration was set to 10 mol % in the polymerization step. The microporous membrane of Example 3 was obtained by the same operation as in Example 1.

[0210] [Example 4]

[0211] In the polymerization step, the solid catalyst component [C] was used instead of the solid catalyst component [A] and the hydrogen concentration was set to 10 mol %, and the ethylene polymer powder of Example 4 was obtained by the same operation as in Example 1. The microporous membrane of Example 4 was obtained by the same operation as in Example 1.

[0212] [Example 5]

[0213] The same polymerization reactor as in Example 1 was used, the polymerization pressure was 0.8 MPa, and the polymerization temperature was maintained at 75°C by jacket cooling. Hexane was supplied to the polymerization reactor at 60 L / h. The liquid component [G] was supplied at 5 mol / h. The solid catalyst component [D] was contacted with 2 L / h of hydrogen in advance and then supplied to the polymerization reactor so that the production rate reached 10 kg / h and the slurry concentration in the polymerization system reached 40% by mass. For the steps after the polymerization reactor, the ethylene polymer powder of Example 5 was obtained by the same operation as in Example 1. The microporous membrane of Example 5 was obtained by the same operation as in Example 1.

[0214] [Example 6]

[0215] In the first polymerization, the same polymerization reactor as in Example 1 was used. The polymerization pressure was 0.5 MPa. The polymerization temperature was maintained at 80°C by jacket cooling. Hexane was supplied at a rate of 20 liters / hour. A solid catalyst component [A] and triisobutylaluminum as a cocatalyst were used. Triisobutylaluminum was added to the polymerizer at a rate of 10 mmol / hour. The solid catalyst component [A] was supplied so that the slurry concentration in the polymerizer reached 40% by mass. The polymerization slurry was extracted so that the liquid level remained constant. Hydrogen was continuously supplied with a pump so that the hydrogen concentration relative to ethylene in the gas phase reached 6 mol%. The polymerization slurry was continuously extracted to a flash evaporator at a pressure of 0.05 MPa and a temperature of 70°C to separate unreacted ethylene and hydrogen. Then in the second polymerization, the polymerization slurry was continuously introduced into a container-type 300L polymerization reactor with a stirring device using a slurry pump. Hexane was supplied to the slurry pump so that the slurry concentration in the polymerizer reached 40% by mass. The polymerization pressure was 0.5 MPa, and the polymerization temperature was maintained at 80°C by jacket cooling. Hydrogen was continuously supplied by a pump so that the hydrogen concentration relative to ethylene in the gas phase reached 25 mol%. The polymerization slurry was continuously extracted to a flash evaporator at a pressure of 0.05 MPa and a temperature of 70°C to separate unreacted ethylene and hydrogen. For the steps after the polymerization reactor, the ethylene polymer powder of Example 6 was obtained by the same operation as in Example 1. The microporous membrane of Example 6 was obtained by the same operation as in Example 1.

[0216] [Example 7]

[0217] In the polymerization step, the ethylene polymer powder of Example 7 was obtained by the same operation as in Example 4 except that the hydrogen concentration was set to 7.5 mol % and propylene was supplied to 0.2 mol %. The microporous membrane of Example 7 was obtained by the same operation as in Example 1.

[0218] [Example 8]

[0219] The ethylene polymer powder of Example 8 was obtained by the same operation as in Example 3 except that the residence time of the polymerization slurry in the buffer tank was set to 1 hour in the polymerization step. The microporous membrane of Example 8 was obtained by the same operation as in Example 1.

[0220] [Comparative Example 1]

[0221] The ethylene polymer powder of Comparative Example 1 was obtained by the same operation as in Example 1 except that the hydrogen concentration was set to 23 mol % in the polymerization step. The microporous membrane of Comparative Example 1 was obtained by the same operation as in Example 1.

[0222] [Comparative Example 2]

[0223] The ethylene polymer powder of Comparative Example 2 was obtained by the same operation as in Example 1 except that the hydrogen concentration was set to 1.5 mol % in the polymerization step. The microporous membrane of Comparative Example 2 was obtained by the same operation as in Example 1.

[0224] [Comparative Example 3]

[0225] The ethylene polymer powder of Comparative Example 3 was obtained by the same operation as in Example 3 except that the slurry concentration in the polymerization vessel was adjusted to 25% by mass in the polymerization step. The microporous membrane of Comparative Example 3 was obtained by the same operation as in Example 1.

[0226] [Comparative Example 4]

[0227] The ethylene polymer powder of Comparative Example 4 was obtained by the same operation as in Example 3 except that the polymerization slurry was not heated and transferred to the centrifuge in the polymerization step. The temperature of the polymerization slurry supplied to the centrifuge was 55° C. The microporous membrane of Comparative Example 4 was obtained by the same operation as in Example 1.

[0228] Table 1 shows the physical properties of the ethylene polymer powders of Examples 1 to 8 and Comparative Examples 1 to 4, and the evaluation results of the microporous films.

[0229]

[0230] This application is based on Japanese Patent Application (Japanese Patent Application No. 2016-218190) filed on November 8, 2016, the contents of which are incorporated herein by reference.

[0231] Industrial Applicability

[0232] The ethylene polymer of the present invention has excellent heat resistance, so the film, microporous membrane, etc. containing the ethylene polymer have excellent heat shrinkage resistance. In particular, when forming a microporous membrane, annealing can be performed at high temperature in a short time while maintaining the porosity, and can be suitably used for microporous membranes requiring high productivity, so it has high industrial practicality.

Claims

1. An ethylene polymer, wherein The ethylene polymer does not contain a comonomer unit, or the content of the comonomer unit in the ethylene polymer is 0.01 mol% or more and 5 mol% or less, The weight average molecular weight (Mw) of the ethylene polymer is 200,000 or more and 1,500,000 or less, The molecular weight distribution (Mw / Mn) of the ethylene polymer is 5 or more and 15 or less, The content of one or more elements selected from the group consisting of Ti, Mg and Al is 50 ppm or less, The ratio D90 / D10 of the particle size of the ethylene polymer measured by a laser particle size analyzer is 1.30 to 1.80, In the case of a three-component approximation of the free induction decay at 130° C. measured by a solid echo method of pulsed NMR, the proportion of the component with the lowest mobility (α130) is 40% or more and 60% or less, and the ratio (β / γ) of the proportion of the component with intermediate mobility (β) to the proportion of the component with the highest mobility (γ) is 1.3 or more and 3.0 or less, The solid echo method using pulsed NMR is measured under the following conditions: Observation core: 1 H Determination: T2 Determination method: solid echo method Pulse width: 2.2μs~2.3μs Pulse interval: 7.0μs~9.2μs Cumulative times: 256 times Measuring temperature: 30℃, 50℃, 70℃, 90℃, 110℃, 130℃, where the measuring temperature is the temperature inside the sample. After the device temperature reaches the set temperature for 5 minutes, adjust the device temperature so that the internal temperature of the sample reaches the measuring temperature, and start the measurement. Repeat time: 3s Analysis method: Use equation 1 and analysis software IGOR Pro6.3 to fit the three components. Formula 1 M(t)=αexp(-(1 / 2)(t / T α ) 2 )sinbt / bt+βexp(-(1 / Wa)(t / T β ) Wa )+γexp(-t / T γ ) in, α: The composition fraction of α component, expressed in %. T α : relaxation time of the α component, in milliseconds β: The composition fraction of β component, expressed in %. T β : relaxation time of the β component, in milliseconds γ: The composition fraction of the γ component, expressed in %. T γ : relaxation time of the γ component, in milliseconds t: observation time, in milliseconds Wa: Shape factor b: shape coefficient.

2. The ethylene polymer according to claim 1, wherein The ratio (α130 / α30) of the ratio of the component with the lowest motility (α130) measured at 130° C. to the ratio of the component with the lowest motility (α30) measured at 30° C. by the solid echo method of the pulsed NMR is 0.1 or more and 0.65 or less.

3. The ethylene polymer according to claim 1, wherein The weight average molecular weight (Mw) of the ethylene polymer is 250,000 or more and 800,000 or less.

4. The ethylene polymer according to claim 1, which is in the form of powder. 5 . A stretched molded product comprising the ethylene polymer according to claim 1 . 6 . A microporous membrane comprising the ethylene polymer according to claim 1 .